Isolation And Sensitivity Test of Heterotrophic Bacteria From Marine and Estuary Waters of Low Salinity In Siak against Pathogenic Bacteria - Rizki Hamdani; Feliatra Feliatra; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             Heterotrophic bacteria are a bacteria that use organic matter as a source of nutrients. It also has potential as antibacterial to pathogenic bacteria. The research was conducted from June to September 2017. The aim of this research was to determine the ability of bacterial isolates to inhibit the growth of pathogenic bacteria (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp.) and determine the species of haterotrophic bacteria in the research area based on PCR method of 16S rRNA sequence. The results showed that twenty five pure bacteria isolates and only ten isolates could be sequenced. Bacterial isolates H2, H4, H8, H10, H12, H15, H16, H17 and H24 were able to inhibit the growth of pathogenic bacteria and were classified into three categories namely strong category (10-20 mm), medium category (5-10 mm) and weak category (≤ 5 mm). Based on the 16S rRNA analysis, it was found that ten identified isolates included Bacillus sp., Bacillus cereus, and Pseudomonas aeruginosa with a homology level of 81-99%. Based on the results of simple linear regression test showed the relationship between the number of heteretrophic bacteria with environmental parameters measured in the very weak category (r = 0,19). Keywords: heterotrophic bacteria, antibacterial, moleculer analysis, 16S rRNA